The Performance Comparison of the Participation Banks Acting in Turkey via Grey Relations Analysis Method - İlker Sakinç; Merve Gülen (Journal of Economic and Social Thought, 2014)
“Participation Banks” are the final review process of the banking sector that have become indispensable for the economy of countries worldwide. Although participation banks do not have a long history, they were included in the Bank Law of 2005, and these banks are getting more attention each day. Since participation banks are perceived as alternative for conventional banks, the performance comparisons of participation banks are important for managers and investors. The purpose of this study is to compare the performances of the participation banks operating in Turkey via Grey Relational Analysis Method. In order to do this, 15 ratios which show the capital adequacy, liquidity, asset quality and profitability criteria years have been determined using 4 year-data of the participation banks from the years 2010 – 2013. Participation banks' performances have been compared using the results of the analysis, with the help of determined ratios. The rank obtained from the results of the analysis is; Kuveyt Türk Participation Bank, Türkiye Finans Participation Bank, Albaraka Türk Participation Bank and Asya Participation Bank. At the end of the study, capital adequacy has been determined as the dominant ratio among all the ratios which affect the performances of participation banks.
Keywords: G14; C67; G20; 330; Participation Banks; Grey Relation Analysis; Performance Analysis; Capital Proficiency Ratios; Financial Performance; Islamic Finance